DESIGN LEARNING OF ARITHMETIC SEQUENCE USING STAIR CONTEXT TO SUPPORT STUDENTS' CONCEPTUAL UNDERSTANDING - Danil C, Fransisco; Zulkardi, Zulkardi; Susanti, Ely; Meryansumayeka, Meryansumayeka (FKIP Universitas Muhammadiyah Tangerang, 2025)
AbstractThis research aimed to design arithmetic sequence learning based on Indonesian Realistic Mathematics Education (PMRI) with the context of stairs to support students' conceptual understanding. The study employed a design research methodology, structured into three key phases: the preliminary design, the design experiment, and the retrospective analysis. The research was conducted on grade 10 students of MA Al-Ittifaqiah Indralaya using Student Activity Sheets (SAS) designed based on the PMRI approach.The results showed that the context of the stairs was effective in helping students recognize the arithmetic sequence pattern concretely. In the initial activity, students were able to observe and record the pattern of staircase height and understand the fixed difference between stairs. However, most students struggled to construct a general formula in the form of formal symbols, although they managed to calculate patterns for complex cases such as the 901st or 2001st stair logically. This difficulty prompted a revision of the SAS to simplify the symbols and questions and to use concrete terms that were easier for students to understand.Revisions to the lesson design included the removal of confusing symbols, the reduction of repetitive problems, and a stepwise approach to linking concrete patterns with formal symbols. This study concluded that although the PMRI approach was effective in improving students' understanding of the concept of arithmetic sequences, further guidance was needed to improve students' symbolic ability. The findings contributed to the development of learning designs that were contextual, effective, and relevant to students' needs.